Are we there yet? Localisation as the journey towards locally led practice: models, approaches and challenges - and Baguios, Arbie; King, Maia; Martins, Alex; Pinnington, Rose (ODI, 2021)
Localisation and locally led international development practice has long been discussed, but has still not been delivered. Systemic barriers have posed challenges, and the term itself is contested. Now, the last tumultuous 18 months could provide a critical juncture to finally move forward with this crucial agenda. The pandemic has highlighted structural inequalities in the global system, and disrupted ways of working in the international development sector. The Black Lives Matter movement has brought conversations about racism and colonialism to the fore. And the climate crisis has highlighted the need for global action on humanity’s challenges that remain rooted in local realities. The emerging analysis in this review aims to set out the key issues in this agenda, building on a wealth of existing knowledge. It aims to span sectors, highlighting many new and existing models and approaches in the humanitarian, development, philanthropic and private sectors. It reviews the barriers and challenges to localisation and locally led practice, with a view to informing a campaign for systemic change to move forward with this agenda. The review is based on: a rapid review of the literature and evidence on localisation and locally led practice; two consultations with over 100 total participants, targeted at Global South actors; and analysis of 28 existing models and approaches.